Moldova Trade Study : Note 2. Is the DCFTA Good for Moldova? Analysis of Moldova’s Trade Options Using a Dynamic Computable General Equilibrium Model - World Bank (World Bank, Washington, DC, 2016)
Moldova’s recent Association Agreement with the European Union (EU), which includes a Deep and Comprehensive Free Trade Agreement (DCFTA), represents an important opportunity, as well as challenges. This analytical document has been commissioned by the World Bank Group to provide insights into potential outcomes of the DCFTA and of other trade options that Moldova has, using a Dynamic Computable General Equilibrium (DCGE) model calibrated to its economy. This paper begins by describing the general trends in economic relations between Moldova and the EU over the past 10 years, with an emphasis on trade, as well as Foreign direct investment (FDI) and labor migration. This section includes some additional facts and details that complement the Trade Competitiveness Diagnostic. In the second section, the paper presents the main elements of the DCFTA and highlights the trade commitments and concessions that the EU and Moldova undertook. It also includes a short review of available literature on the ex-ante or ex post impact assessments of other Association Agreements between the EU and third countries that have been done using CGE models. The third section presents key features of the DCGE and discusses the data used for assembling the Social Accounting Matrix (SAM). Then, the main features of the simulated trade scenarios are presented. Finally, this paper discusses the DCGE simulation results, including the effects of the various scenarios on welfare, trade, and economic activity level. Some distributional impacts are also brought into discussion. The final section concludes and makes several recommendations.